Clinical and Biomechanical Outcomes following Knee Extensor Mechanism Reconstruction - Berkcan Akpinar, M.D; Samuel Baron, B.S; Michael J. Alaia, M.D; Laith M. Jazrawi, M.D (Elsevier, 2020)
Purpose: To evaluate clinical and biomechanical outcomes after knee extensor mechanism reconstruction (KEMR). Methods: Patients who underwent KEMR at our institution from 2011 to 2018 were identified. Patient-reported outcomes (Kujala, Lysholm, Tegner Activity Scale) were compiled at clinical follow-up. Isokinetic testing was conducted using the BioDex system 4 pro dynamometer at slow (60°/s), intermediate (180°/s), and fast (300°/s) speeds in a 9-patient subset. Results: From 2011 to 2018, 12 patients (12 knees, 10 male, 5 right, mean age: 54.3 ± standard deviation: 15.2 years) with KEM injuries requiring tendon reconstruction with a 1-year minimum follow up were identified. Postoperative follow-up was 42.6 months (range: 12.0-93.0 months). Procedures included patellar (7) and quadriceps tendon reconstruction (5). Postoperative versus preoperative Tegner Activity Scale scores demonstrated significant improvement (3.5 ± 2.5 vs 1.5 ± 1.2, n = 8, P = .05). Postoperative versus preoperative Kujala scores significantly improved (70.3 ± 11.7 vs 43.6 ± 15.7, n = 8, P = .010). There was significant improvement in preoperative to postoperative KEMR extension lag (29.4 ± 22.2° vs 0.83 ± 1.9°, P = .002). Clinically, there was no difference in passive range of motion between the operative and contralateral knee. BioDex testing demonstrated decreased maximum work generated from the operative versus contralateral knee at slow (70.4 ± 30.4 Joules vs 101.9 ± 40.6 J; P = .028), intermediate (52.0 ± 45.4 J vs 69.8 ± 63.7 J; P = .038), and fast (43.8 ± 41.7 J vs 57.5 ± 53.8 J; P = .050) speeds. Range of motion was less in the operative versus contralateral knee at all speeds: P = .011, .038, and .024. The average peak torque generated per body weight was smaller in the operative versus contralateral knee at slow speed (P = .038). Conclusions: Patients undergoing KEMR in this study have significantly improved clinical outcomes despite having strength deficits that persist postoperatively. Level of Evidence: Therapeutic Case Series, Level IV.